Risk Factors for Recurrent Febrile Convulsions in Children - Alwan, Yusra Fayyadh; Hussein, Hafadh Jaleel (AL-Kindy College Medical Journal, 2013)
Background: Febrile convulsions are the most frequent type of seizures in children under 6 years of age. Significant percentage of these children will later suffer from recurrence of febrile convulsion.Objectives: To identify the main risk factors for recurrent febrile convulsions in children.Methods: we carried out a case control study involving 89 children those who experienced first attack of febrile convulsions and 92 children with recurrent attack of febrile convulsions. The study was conducted in Central Children Teaching Hospital, Baghdad during the period 2006- 2007. Results: Compared to children with first attack of febrile convulsion, children with recurrent seizures were younger at onset (4- 12m) (67% vs. 44%), mainly male (70% vs. 51%) and had more often family history (first degree relative) history of epilepsy, low degree of temperature (45% vs. 23%) and frequent febrile illnesses (83% vs. 50%). second degree family history of febrile convulsion and onset of febrile convulsion in relation to onset of fever and type of convulsion (simple vs. complex) were not significant risk factors.Conclusions: Awareness of these risk factors should lead pediatricians to suggest administration of short course of diazepam at onset of each febrile illness to prevent recurrent febrile convulsions. Also, public education on recurrent febrile convulsions is needed.